The Effect of Food on the Incident of Hypertension - Restia; Yusra Pintaningrum; Cut Warnaini (Jurnal Biologi Tropis, 2023)
Hypertension is the condition of a person whose blood pressure is above the normal limit according to medical regulations, namely greater than 140/90 mmHg. Hypertension is a major risk factor for cardiovascular disease, stroke, kidney failure and the main cause of death throughout the world. Consuming foods that are high in fat, carbohydrates, fiber and sodium can increase the occurrence of hypertension. This study aims to determine the effect of food on the incidence of hypertension. This research uses several relevant literature from various references and focuses on risk factors for hypertension, one of which is food. The references used came from searches on NCBI, Pubmed, Google Scholar, and Science Direct and 25 data-based sources were obtained. The results of this research are that there is an influence between food sources such as carbohydrates, fat and sodium which can increase the occurrence of hypertension and high fiber consumption which helps to reduce the occurrence of hypertension. Excessive sodium consumption causes the sodium concentration in the extracellular fluid to increase. And consuming excess carbohydrates can cause triglyceride levels in the blood to increase, causing carbohydrates to be converted into fat. High fat levels can cause atherosclerosis which will ultimately lead to hypertension. The conclusion is that consuming foods high in carbohydrates, fat and sodium can cause hypertension and high fiber consumption can help minimize the occurrence of hypertension.